Recent Patents on the Structure of High-Speed Motorized Spindle - Dai, Ye; Wei, Wen-Qiang; Zhang, Xue-Liang; Qi, Yun-Shan (Recent Patents on Mechanical Engineering, 2019)
Background: As one of the core components of high-speed CNC machine tool, high-speed motorized spindle is the core functional component of high precision CNC machine tool, which has become the key research and development object of the world. Objective: By comparing and discussing the patents of high-speed motorized spindle, some valuable conclusions have been drawn to predict the future research and development of high-speed motorized spindle. Methods: By analyzing the characteristics of high-speed motorized spindle structure, the influence of high-speed motorized spindle on high-speed machining technology was explicated. Combining with the key technology of high-speed motorized spindle, the patents related to high-speed motorized spindle structure were used for investigation. Results: With the rapid development of high-speed cutting and numerical control technology and the need of practical application, the requirement for high-speed spindle performance has increased. Motorized spindle technology has the characteristics of high speed, high strength, high power, high torque and low speed, high precision, high reliability and long life, offering diversified bearing and lubrication cooling methods and serving as an intelligent system. Conclusion: The different levels of improvement and renovation of the structure with high-speed motorized spindle, by adding lubrication and cooling device to the spindle have improve the performance of spindle, addressing the loopholes in the technology and making it more practical.
Keywords: modern manufacturing industry